Influence of Lithium Iron Phosphate Positive Electrode Material to Hybrid Lithium-Ion Battery Capacitor (H-LIBC) Energy Storage Devices. Issue 11 (1st January 2018) - Yan, J.; Chen, X. J.; Shellikeri, A.; Du, T.; Hagen, M.; Zheng, J. P.; Cao, W. J.
Abstract : Lithium-ion capacitor (LIC) is known as a huge step after lithium-ion battery (LIB) and ultracapacitor by combining both pre-lithated graphite/hard carbon negative electrode (NE) and activated carbon positive electrode (PE) in its design. And LIC can realize high energy and power densities as well as fast charging property with extreme long cycling life. In this paper, a new cell design based energy storage device named hybrid lithium-ion battery capacitor (H-LIBC) will be reported. By adding different amount of lithium iron phosphate (LiFePO4, LFP) in LIC's PE material activated carbon, H-LIBC will show various amount of battery properties when comparing with standard LIC. That is to say, LFP can actually improve LIC's battery side and leaves more energy storage space. In addition, the remaining LIC materials can still maintain its fast charging property and long cycle life. In this paper, electrode will be examined by scanning electron microscope (SEM) as well as energy dispersive X-ray (EDX) analyzer. Later, 3-electrode cells will be used to demonstrate LFP's influence on standard LIC and they will be fabricated after electrode manufacturing. In the meantime, a new calculation method to determine the amount of pre-loaded ultra-thin lithium to the NE will be illustrated. Furthermore, nine-layer laminated hybrid cells will be compared with same size 200F standard LIC to see the capacitance and energy density change. High rate cycle life results are also included.